The Effect of Internal Communication and Work Discipline on Employee Performance in the Protocol and Leadership Communication Section of the Regional Secretariat of Central Lampung Regency - Arini, Nia Nur; Fauziah, Hujaimatul (Saburai International Journal of Social Sciences and Development, 2023)
The objectives to be achieved in this study were to determine: 1. the effect of internal communication on employee performance in the Protocol and Communication Section of the Central Lampung Regency Regional Secretariat, 2. the effect of work discipline on employee performance in the Protocol and Communication Section of the Central Lampung Regency Regional Secretariat, 3. the effect of internal communication and work discipline together on employee performance in the Protocol and Communication Section of the Central Lampung Regency Regional Secretariat. Data on employees of the Protocol and Communication Section of the Regional Secretariat of Central Lampung Regency totaled 44 people and became the population in this study, while the sample in the study was 31 respondents using slovin. The analytical tools used are validity test, reliability test, normality test, multiple linear regression test, T test, F test and determination coefficient test. The results of the study are 1. there is an effect of internal communication (X1) on employee performance (Y) in the Protocol and Communication Section of the Central Lampung Regency Regional Secretariat, 2. there is an effect of work discipline on employee performance in the Protocol and Communication Section of the Central Lampung Regency Regional Secretariat, 3. there is an effect of internal communication and work discipline together on employee performance in the Protocol and Communication Section of the Central Lampung Regency Regional Secretariat.